Low fertility in China: Trends, policy and impact - Baochang Gu (Asia-Pacific Population Journal, 2007)
China currently is the country with the largest population in the world. The Fifth National Population Census in 2000 reports that the total population of mainland China stands at 1.27 billion (Zhuang and Zhang, 2003), while the 1 Percent National Population Sample Survey (mini-census) carried out in November 2005 reports the total population to be at 1.31 billion (National Statistics Bureau (NSB), 2006).1 China is also the country with the most stringent and government-directed family planning programme and fertility policy, having experienced a dramatic decline in fertility from 5 to 6 children per woman in the 1950s to less than 2 in recent years. The 2000 census reports China’s total fertility rate (TFR) to be at 1.4 (NSB, 2003). The rapid changes occurring in China’s population dynamics call for a review of the fertility transition in China in terms of trends, policy and impact. This article will first discuss the population dynamics ongoing in China in terms of growth, birth rate and fertility and then examine the fertility policy implemented by the Government of China, before exploring the impact of fertility decline in terms of population ageing, gender equality, sex ratio at birth and labour supply.